Is x = 6 a solution to the equation 5(x – 3) = x + 13?
Follow the steps to find out.
1. Rewrite the equation 5(x – 3) = x + 13 with 6 substituted for x. Write a question mark over the equal sign to show that you're testing to see if the equation is true.

ill give brainliest

Respuesta :

Yes, both equations will always work, but yes, at times it is more logical to use one over the other. for instance:

x-4y=6

x+4y=12

we see here that elimination would best fit:

x+x+4y-4y=6+12

or:

x=2y-3

7x+3y-81=23

substitute (2y-3) for x.

Also, once you have a single placeholder, put it ito quadratic form (ax^2+bx+c=0)

and use the quadratic formula:

x=(-b±sqrt(b^2-4ac))/2a

Answer:

yes

Step-by-step explanation:

ACCESS MORE